PEM fuel cell multi-phase system - Hard, Kevin (2005)
This thesis presents an experimental investigation into the feasibility of using a functionally thermal fluid to enhance the performance of a Proton Exchange Membrane (PEM) Fuel Cell. Specifically, a fluid was developed that utilised a liquid-solid phase change to enhance heat transport within the fuel cell. Increasing the convective heat transfer coefficient could permit the use of smaller volumetric flow rates and reduce pumping power.